Migration of Indwelling Central Venous Catheter and Fatal Hydrothorax - Shagufta Jabeen; Ghulam Murtaza; Muhammad Zubair Hanif; Antonino Morabito; Basem Khalil (Georg Thieme Verlag KG, 2013)
Abstract Central venous catheter complications can be related to insertion, indwelling, or extraction. Most of the times, immediate complications are anticipated and managed; whereas, delayed complications can go unnoticed. In the case discussed here, migration and dislodgement of catheter tip resulted in delayed hydrothorax and sudden death of a 9-month-old female infant.